Italy : Technical Note on Stress Testing The Banking Sector. (IMF Staff Country Reports; Country Report ;, 2013)
This Technical Note elaborates the recommendations made in the Financial Sector Assessment Program for Italy in the areas of contingency planning, crisis management, and bank resolution. The note sets out a brief overview of the impact of the global financial crisis in Italy and how the authorities handled the crisis. It analyzes the institutional framework and domestic and cross-border coordination arrangements. The supervisory approach to intervene with potential problem banks at an early stage is examined. The note also covers crisis management tools, including official financial support measures, the resolution framework, and the deposit guarantee framework.